Conducta obstétrica en adolescente de 15 años con 40 semanas de gestación y shock hipovolémico - Euvin Alvear, Jorge Andrés (2021)
Adolescence is a stage of growth and development that ranges from 10 to 19 years according to the World Health Organization (WHO). Early pregnancy, also called teenage pregnancy, is one that occurs when a woman is in her puberty stage. Early pregnancy poses specific risks that are added to those derived from physiological immaturity in adolescents. Hypovolemic shock is a syndrome that occurs due to the reduction of blood volume, which is triggered by an inadequate acute systemic perfusion due to an imbalance between the demand and supply of oxygen to the tissues, either due to insufficient supply or misuse at scale cellular. There are established amounts in blood loss so that Postpartum Hemorrhage can be considered, during a vaginal delivery if the loss is 500 ml or exceeds this amount and in caesarean section when exceeding 1000 ml, or any blood loss that produces hemodynamic instability should be considered a PPH. The case of a 15-year-old patient with no novelty in the history is presented, who is brought in from another health home and comes because of bleeding in the abundant genital area after a complicated physiological puerperium, she acts under a red code protocol, she is prepared for surgery under anesthesia, lesions in the genital area are repaired.